Jeremiah A study in ancient Hebrew rhetoric - Lundbom, Jack R. (Indiana Eisenbrauns, 1997)
Originally presented as the author's thesis--Graduate Theological Union, Berkeley, 1973.
Keywords: Bible - Jeremiah. Bible. -- Jeremiah -- Language, style. Bible. -- Jeremiah -- Criticism, interpretation, etc. RELIGION -- Biblical Studies -- Prophets